A recent update on green synthesized iron and iron oxide nanoparticles for environmental applications. (December 2022) - Selvaraj, Raja; Pai, Shraddha; Vinayagam, Ramesh; Varadavenkatesan, Thivaharan; Kumar, Ponnusamy Senthil; Duc, Pham Anh; Rangasamy, Gayathri
Abstract: Nanotechnology is considered the budding discipline in various fields of science and technology. In this review, the various synthesis methods of iron and iron oxide nanoparticles were summarised with more emphasis on green synthesis – a sustainable and eco-friendly method. The mechanism of green synthesis of these nanomaterials was reviewed in recent literature. The magnetic properties of these nanomaterials were briefed which makes them unique in the family of nanomaterials. An overview of various removal methods for the pollutants such as dye, heavy metals, and emerging contaminants using green synthesized iron and iron oxide nanoparticles is discussed. The mechanism of pollutant removal methods like Fenton-like degradation, photocatalytic degradation, and adsorption techniques was also detailed. The review is concluded with the challenges and possible future aspects of these nanomaterials for various environmental applications. Graphical abstract: Image 1 Highlights: Various synthesis methods of iron and iron oxide nanoparticles are reviewed. Green synthesis mechanism of iron and iron oxide nanoparticles is outlined. Removal of various pollutants by iron and iron oxide nanoparticles are briefed. Various magnetic properties of the nanoparticles have been discussed. Various mechanisms of pollutant removal has been described.